Comparative Evaluation of Resin Dentin Interface using Universal and Total- Etch Adhesive Systems on Sound and Eroded Dentin: In Vitro Study - Kanniappan, Ghayathri; Hari, Padmini; Jujare, Ravikanth H. (European Journal of Dentistry, 2021)
Objective This study aimed to compare the resin-dentin interface of sound and eroded dentin using universal and total-etch adhesive systems.Materials and Methods Forty caries-free extracted human premolars were collected, and the occlusal surfaces were ground by using slow speed diamond disc with copious water supply until a flat superficial dentin was exposed. The test group underwent erosive cycle (n = 20), and another group (n = 20) was reserved for control group. Erosive protocol consisted of immersion in 1.23% citric acid for 1 minute every 12 hours and stored in artificial saliva. Both the control and eroded teeth were further subdivided (n = 10) for composite restoration by using either self-etch or total-etch systems. Then the tooth samples were sectioned longitudinally and observed under confocal laser scanning microscope at ×10 magnification to evaluate resin tag length and hybrid layer thickness.Statistical Analysis The data obtained were analyzed by using independent t-test.Results The highest mean value of the resin tag length and thickness of hybrid layer was observed with total-etch system in sound dentin group compared with other groups (p < 0.001).Conclusion The resin-dentin interface of sound dentin was found to be better than eroded dentin by using total-etch system. The resin-dentin interface of eroded dentin was superior to sound dentin by using self-etch adhesive system.
Keywords: confocal laser scanning microscope; eroded dentin; resin tag length; total-etch adhesive; universal adhesive